Folate supplementation in pregnancy (International Journal of Scientific Research and Management (IJSRM), 2021)
Objectives: To determine the prevalence of low, normal and high folate levels in Omani population. Folate supplement given routinely during pregnancy. Folate added into multi-vitamins supplement as well as into food products. This leads to decrease the prevalence of low folate or increase prevalence of people with excess folate. Low and high folate level leads to adverse side effects. Methods: 3706 folate samples analyzed in Cobas e 601 chemical analyzer. The results separated into three main groups (low, normal and high). Results: Only 0.3% of the study sample shows low folate level. Five (0.2%) out of 2335 female samples show low folate level. Three (0.2%) out of 1371 male samples shows low folate level. Conclusion: Routine folate intake during pregnancy, supplement to the general population for wellbeing and food fortification might lead to excess folate status. Folate testing before supplementation help in avoiding high folate adverse effects.